Epidemiological characteristics of multiple sclerosis in Tomsk Region and their dynamics for last 30 years - V. M. Alifirova; M. A. Titova (Бюллетень сибирской медицины)
The Tomsk Region is a zone of average risk multiple sclerosis (MS), prevalence makes 27.1 cases on 100 000 people. During the period with 1980 for 2010 variety of morbidity from 0.4 (1992) to 4.1 (2003) on 100 000 people. The lowest morbidity was in period with 1991 for 1995 and makes 1.8 on 100 000 people, and the highest in the rage from 2001 for 2005 — 3.1 on 100 000 people. Last 5 years in the TomskRegion to increase ofmorbidityis observed.